2023
DOI: 10.1111/nph.18805
|View full text |Cite
|
Sign up to set email alerts
|

A non‐homogeneous model of chromosome‐number evolution to reveal shifts in the transition patterns across the phylogeny

Abstract: Changes in chromosome numbers, including polyploidy and dysploidy events, play a key role in eukaryote evolution as they could expediate reproductive isolation and have the potential to foster phenotypic diversification. Deciphering the pattern of chromosome-number change within a phylogeny currently relies on probabilistic evolutionary models. All currently available models assume time homogeneity, such that the transition rates are identical throughout the phylogeny.Here, we develop heterogeneous models of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Carex-the largest genus in Cyperaceae-is particularly well suited to studying the effect of dysploidy on plant diversification because all Carex have holocentric chromosomes, the genus represents 40% of the third most species-rich monocot family (among the tenth in angiosperms, POWO 2023) and well-developed phylogenetic and chromosome number datasets for the genus to facilitate macroevolutionary studies (Martín-Bravo et al 2019. In Carex, karyotype evolves mainly through fusion, fission, and translocations, in contrast to in other sedge lineages where karyotype evolves through both dysploidy and polyploidy (Márquez-Corro, Martín-Bravo, Spalink, Luce ño & Escudero 2019, Elliott et al 2022, Shafir et al 2023. Carex also has exceptional variability in chromosome number, ranging from 2n = 10 to 2n = 132 (Márquez-Corro et al 2021).…”
Section: Dysploidy and Holocentric Chromosomesmentioning
confidence: 99%
“…Carex-the largest genus in Cyperaceae-is particularly well suited to studying the effect of dysploidy on plant diversification because all Carex have holocentric chromosomes, the genus represents 40% of the third most species-rich monocot family (among the tenth in angiosperms, POWO 2023) and well-developed phylogenetic and chromosome number datasets for the genus to facilitate macroevolutionary studies (Martín-Bravo et al 2019. In Carex, karyotype evolves mainly through fusion, fission, and translocations, in contrast to in other sedge lineages where karyotype evolves through both dysploidy and polyploidy (Márquez-Corro, Martín-Bravo, Spalink, Luce ño & Escudero 2019, Elliott et al 2022, Shafir et al 2023. Carex also has exceptional variability in chromosome number, ranging from 2n = 10 to 2n = 132 (Márquez-Corro et al 2021).…”
Section: Dysploidy and Holocentric Chromosomesmentioning
confidence: 99%
“…For example, polyploidy occurrence is strikingly low in the Carex genus, despite the high volume of species diversity (∼2,000) and an exceptional chromosome number variation (2 n = 10 to 132) ( Márquez-Corro et al 2021 ). However, it may not hold for other Cyperid species, as the chromosome number could evolve at heterogeneous rates along different clades ( Márquez-Corro et al 2019 ; Shafir et al 2023 ). Notably, previous studies have provided some clues for polyploidization in the Schoenoplectus genus.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, botanists often study chromosome number evolution within their clades of interest. The Mayrose group at Tel‐Aviv University has developed several open resources that facilitate research into the diversity and evolution of chromosome number in plants: (1) chrom E vol (Mayrose et al ., 2010; Glick & Mayrose, 2014; Shafir et al ., 2023), a program that models the evolution of chromosome numbers along a phylogeny; (2) The Chromosome Counts Database (CCDB; Rice et al ., 2015), a regularly updated database of plant chromosome counts; and (3) O ne T wo T ree (OTT; Drori et al ., 2018), an online resource for automated phylogeny reconstruction.
‘P loi DB is a highly useful synthesis of existing resources that will help generate hypotheses and enable novel, broad‐scale studies of polyploidy in spermatophytes.’
…”
mentioning
confidence: 99%
“…In some cases, the authors rightly excluded datasets where this modeling approach has been shown to be inadequate (e.g. in Cyperaceae, which have holocentric chromosomes and heterogeneous patterns of dysploid evolution; Shafir et al ., 2023). This approach may also fail in groups where other data are critical for understanding the history of WGDs.…”
mentioning
confidence: 99%